2016
DOI: 10.2337/dc15-2577
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes and Polycystic Ovary Syndrome: Systematic Review and Meta-analysis

Abstract: A few small studies have reported increased prevalences of polycystic ovary syndrome (PCOS) and symptoms of androgen excess in women with type 1 diabetes. PURPOSEWe performed a systematic review and meta-analysis of studies evaluating androgen excess symptoms and PCOS in women with type 1 diabetes. DATA SOURCESThe Entrez-PubMed and Scopus electronic databases were used. STUDY SELECTIONWe selected studies addressing androgen excess signs, symptoms, and disorders in girls, adolescents, and adult women with type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 65 publications
3
55
0
2
Order By: Relevance
“…In a recent meta -analysis, Escobar -Morreale et al 18 reported that the development of full PCOS phenotype with its symptoms in girls with T1DM is probably a long -term process. Thus, cardiometabolic consequences are observed later in life, and prospective studies are required to further investigate this issue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent meta -analysis, Escobar -Morreale et al 18 reported that the development of full PCOS phenotype with its symptoms in girls with T1DM is probably a long -term process. Thus, cardiometabolic consequences are observed later in life, and prospective studies are required to further investigate this issue.…”
Section: Resultsmentioning
confidence: 99%
“…17 It has been reported that the prevalence of PCOS in adult women with T1DM is significantly higher than in controls and reaches 40%, according to the Rotterdam diagnostic criteria. 18 Despite limited evidence, PCOS appears to be among the most common endocrine disorders in women of reproductive age with T1DM. 18 Patients with T1DM also have an increased risk of endothelial dysfunction, premature atherosclerosis, and CV diseases.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a high percentage (over 70%) of women with type 1 diabetes suffer from menstrual cycle disorders, hyperandrogenism and polycystic ovary syndrome (PCOS), it is recommended to carefully assess and possibly correct gestational age with the use of ultrasound examination during the first trimester and to compare the result with the date of last menstrual period [43].…”
Section: Ultrasonographic Examination and Monitoring Of Fetal Well-beingmentioning
confidence: 99%
“…It seems appropriate to mention that girls who have type-1 DM can also have hyperandrogenism (peculiar trait of PCOS) caused by an excessive administration of exogenous insulin, resulting in a hyperstimulation of theca cells in ovary, which produce sexual hormones [3].…”
Section: Introductionmentioning
confidence: 99%